Role of Alcian Blue Stain in Differentiating Prostatic Adenocarcinoma from Nodular Hyperplasia of Prostate - Al Imran, Zahir; Asafudullah, S M; Khanam, Khadiza; Sultana, Arefa; Majumder, Swapna; Aynunnahar, Mst (TAJ: Journal of Teachers Association, 2023)
Objective: Enlargement of prostate is one of the leading cause of morbidity in men. Alcian Blue stain demonstrates that the acidic mucin is present in prostatic adenocarcinoma but absent in nodular hyperplasia of prostste. So this histochemical marker can be used in distinguishing them. This study aims to determine the role of Alcian Blue stain in differentiating prostatic adenocarcinoma from the nodular hyperplasia of prostate. Materials and Methods: This cross-sectional study was conducted in the Department of Pathology, Rajshahi Medical College, Rajshahi and in the Department of Pathology, Bangabandhu Sheikh Mujib Medical University (BSMMU) during the period of March 2018 to February 2020. Specimens were processed routinely for Haematoxilin and Eosin stain. The Alcian Blue stain was performed to demonstrate the presence of acidic mucin and the findings were categorized as positive or negative staining. Statistical analyses was carried out by using the Statistical package for Social Sciences (SPSS) version 20 for Windows. The components of accuracy test were computed by respective formulae for the tests. Result: The study involved a total 60 specimens of prostatic tissue among which 30 were histopathologically diagnosed cases of prostatic adenocarcinoma and another 30 were histopathologically diagnosed cases of nodular hyperplasia. Among the 30 cases of prostatic adenocarcinoma the acidic mucin was positive in 25 (83.3 %) cases and negative in 5 (16.7%) cases but in nodular hyperplasia it was positive in 8 (26.6%) cases and negative in 22 (73.4%) cases. The sensitivity of Alcian Blue stain in favour of malignancy was 83.3% and specificity was 73.3%. The overall diagnostic accuracy of Alcian Blue stain was 78.3% and it showed a statistically significant difference in staining between the cases of adenocarcinoma and nodular hyperplasia, indicated by p<0.05. Conclusion: Alcian Blue stain has a valuable role in differentiating prostatic adenocarcinoma from the nodular hyperplasia. So it can be used in the diagnosis of prostatic adenocarcinoma. TAJ 2023; 36: No-2: 57-63